Expression of Tim-3 on neutrophils as a novel indicator to assess disease activity and severity in ankylosing spondylitis - Huang, Xuechan; He, Yuebing; Yi, Guanqun; Zheng, Shaoling; Deng, Weiming; Chen, Shuyang; Zhu, Ruiqi; Wang, Yunqing; Chen, Junming; Zheng, Chun; Huang, Zhixiang; Li, Tianwang (Frontiers in Medicine, 2025)
ObjectiveTo investigate the expression of Tim-3 on neutrophils in ankylosing spondylitis (AS) patients and its correlation with disease activity, severity, and inflammatory markers.MethodsSixty-two AS patients from Guangdong Second Provincial General Hospital and 38 healthy controls (HC) were enrolled. Clinical data, physical exams, and laboratory measurements were recorded. Flow cytometry measured Tim-3 and PD-1 expression on neutrophils, real-time PCR quantified mRNA levels and protein expression of Tim-3 was determined by Western blot. We analyzed the correlation between Tim-3 mean fluorescence intensity (MFI) on neutrophils, inflammatory markers, and AS disease activity and severity.ResultsTim-3 expression on neutrophils was higher in AS patients than in HC, showing a positive correlation with erythrocyte sedimentation rate (ESR), c-reactive protein (CRP), and Ankylosing Spondylitis Disease Activity Score (ASDAS). Active AS patients (ASDAS ≥ 1.3) had increased Tim-3 MFI compared to inactive ones (ASDAS < 1.3). Regular treatment with non-steroidal anti-inflammatory drugs (NSAIDs), biological disease-modifying anti-rheumatic drugs (bDMARDs), and conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) over a month significantly reduced Tim-3 MFI in AS patients.ConclusionElevated Tim-3 expression on neutrophils correlates with increased inflammatory markers and AS activity. Treatment lowered Tim-3 MFI, suggesting its potential as an indicator for assessing AS disease activity and severity and as a feedback mechanism to reduce tissue damage from inflammation.